Funding models and expenditures with primary healthcare in Salvador, Bahia, Brazil metropolitan area. (30th September 2020) - Vivas, T; Duarte, M; Pitta, A; Christovam, B
Abstract: Background: The government investments in quality primary healthcare are the basis to strengthening the health systems and monitoring the public expenditure in this area is a way to assess the effectiveness and efficiency of the public health policies. The Brazil Ministry of Health changed, in 2017, the method of onlending federal resources to states and cities seeking to make the public funds management more flexible. This change, however, suppressed mandatory investments in primary healthcare. This research aims to determine the difference of expenditures on primary healthcare in Salvador, Bahia, Brazil metropolitan area before and after this funding reform, seeking to verify how it can impact the quality of primary healthcare services and programs. Methods: This is an ecological time-series study that used data obtained in the Brazil Ministry of Health budget reports. The median and interquartile range of expenditures on primary healthcare (set as the percentage of total public health budget applied in primary care services and programs) of the 13 cities in the Salvador metropolitan area were compared two years before and after the reform. Results: The median of expenditures on primary healthcare in Salvador metropolitan area was 25.5% (13, 9% - 32, 2%) of total public health budget before and 24.8% (20.8% - 30.0%) of total public health budget after the reform (-0.7% difference). Seven cities decreased the expenditures on primary healthcare after the reform, ranging from 1.2% to 10.8% reduction in the primary healthcare budget in five years. Conclusions: Expenditures on primary healthcare in Salvador metropolitan area decreased after the 2017 funding reform. Seven of 13 cities reduced the government investments on primary healthcare services and programs in this scenario. Although the overall difference was -0.7%, the budget cuts ranged from 1.2% to 10.8% in the analyzed period and sample. More studies should assess these events in wide areas and with long time ranges. Key messages: Public health funding models can impact the primary healthcare settings regardless of the health policy. Reforms in the funding models should consider the possible benefits before implementation. Funding models and methods that require mandatory investments in primary healthcare may be considered over more flexible ones.